MENGKREASI KULTUR POSITIF SEKOLAH MELALUI KEPEMIMPINAN BIJAK - Sumardi, Vinsensius (STKIP Santu Paulus Ruteng, 2015)
Abstract: Create Positive School Culture through Wise Leadership. The function of positive school culture as the distinguishing school with the other school meaning sense of identity. The integilibility of identity to created sense of belonging all member’s school. Sense of belonging all member’s to construct individual commitment. The meaning of commitment as a atmosphere all member’s school given capability and dedication for school. The possitve school culture as determinant variable achieving effective and quality school. Contruct of positive school culture is a participation and collaboration process in a community or organization. One of the task leader is to creat positive school culture. School leader demanded perform by wise leadership which not head (brain) considere but to lead by heart (feeling). Keywords: the possitive school culture, wise leadership Abstrak: Mengkreasi Kultur Positif Sekolah Melalui Kepemimpinan Bijak. Kultur sekolah pada fungsinya sebagai pembeda sekolah dengan sekolah lain menegaskan jati diri. Jati diri atau identitas sekolah yang jelas memungkinkan rasa memiliki warga sekolah. Rasa memiliki yang terpatri pada setiap warga sekolah akan menumbuhkan komitmen individu. Komitmen dimaknai sebagai suatu keadaan dimana sleuruh warga sekolah mencurahkan segenap kemampuan dan loyalitasnya untuk sekolah. Kultur sekolah positif menjadi variabel determinan menggapai sekolah efektif dan berkualitas. Mengkonstruksi kultur positif sekolah bukan sekali jadi tetapi merupakan sebuah aktivitas yang menuntut partisipasi dan kolaborasi. Membangun kultur positif sekolah menjadi salah satu tugas pemimpin. Mengkreasi kultur positif sekolah menuntut kepala sekolah tampil dengan kepemimpinan bijak yang tidak hanya mengandalkan kepala (otak) tetapi juga menyertakan hati (perasaan). Kata kunci: kultur positif sekolah, kepemimpinan bijak